Study of Damping Properties of Glass Fibers Reinforced Scrap Rubber Composites Prepared by Simple Mixing - Li, Mingjun; Xu, Yongwen; Qin, Yuancheng; Sun, Yanping (Asian Journal of Chemistry, 2013)
A simple and efficient method was developed to prepare glass fibers reinforced scrap rubber composites by simple mixing. The effect of the concentration and length (L)/diameter (D) on the damping and mechanical properties was studied. The optimization values of the concentration and L/D are determined to be 30 g and 4:1, respectively. The interface topography was also studied by SEM to implore the microstructure and damping mechanism of the composites.